2012
DOI: 10.1177/1756283x12464100
|View full text |Cite
|
Sign up to set email alerts
|

Split dose and MiraLAX-based purgatives to enhance bowel preparation quality becoming common recommendations in the US

Abstract: Abstract:Objectives: Rates of suboptimal bowel preparation up to 30% have been reported. Liberalized precolonoscopy diet, split dose purgative, and the use of MiraLAX-based bowel preparation (MBBP) prior to colonoscopy are recently developed measures to improve bowel preparation quality but little is known about the utilization prevalence of these measures. We examined the patterns of utilization of these newer approaches to improve precolonoscopy bowel preparation quality among American gastroenterologists. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…An over-the-counter PEG product for the management of constipation (PEG-3550) has also been used for colonoscopy preparation [90,107]. A 2013 survey of gastroenterologists revealed that more than one-third recommended PEG-3550 as a bowel preparation to patients, primarily in suburban settings [113]. PEG-3550 is not osmotically balanced, and electrolyte shifts, particularly hyponatremia, may occur, which could cause complications in patients with certain comorbidities [109].…”
Section: Bowel Preparation Regimensmentioning
confidence: 99%
“…An over-the-counter PEG product for the management of constipation (PEG-3550) has also been used for colonoscopy preparation [90,107]. A 2013 survey of gastroenterologists revealed that more than one-third recommended PEG-3550 as a bowel preparation to patients, primarily in suburban settings [113]. PEG-3550 is not osmotically balanced, and electrolyte shifts, particularly hyponatremia, may occur, which could cause complications in patients with certain comorbidities [109].…”
Section: Bowel Preparation Regimensmentioning
confidence: 99%
“…In keeping with our established protocol (Appendix 7) [12], the patient must be NPO for 4 hours prior to the procedure but can have clear liquids prior to that time. The literature suggests that split dose preparations are more effective and better tolerated by patients in general [13,14]. On the other hand patient compliance with split dose prep can be an issue [15].…”
Section: Colonoscopy Preparationmentioning
confidence: 99%
“…15 Split bowel preparation dosing, whereby the patient is instructed to take half the dose the evening before and the remainder on the morning of the examination, has been more successful because of better visualization of the proximal colon and mitigates the risks of noncompliance, fluid shifts, and renal injury in the elderly. 22,23 SEDATION Procedural sedation during endoscopy remains relatively safe with minimal complications. The general risks of sedation include decreased respiratory drive, aspiration, and a greater likelihood of endoscopic injury.…”
Section: Bowel Preparationmentioning
confidence: 99%